Penerapan Pendekatan Permainan Hijau-Hitam Untuk Meningkatkan Hasil Belajar Lari Cepat (Sprint) Siswa SD - Muliadi Muliadi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2017)
Problems in learning the sport Physical Education and Health (PJOK) ran low level learning outcomes (Sprint students. The problem is formulated as follows How Application-Black ijau game approach to improving student learning outcomes run V SD State 12 Manurunge District of Tanete Riattang Bone regency objective of the research is to describe the application to approach the game Green Black, to improve learning outcomes sprint (Sprint) fifth grade students of SD Negeri 12 Manurunge District of Tan Riattang Bone regency. the focus in the classroom action research is the application of the approach Black-green game and improve learning outcomes sprint (sprint) student. Subjects were students of class V SD Negeri 12 Manurunge District of Tanete Riattang Bone regency, Data collection techniques in this study is the observation and tests. Mechanical Analysis Data are data reduction, data presentation , Withdrawal Conclusion Outcome research that the application of the Black-green game approach can improve learning outcomes sprint (Sprint) Class V students of SD Negeri 12 Manurunge District of Tanete Riattang Bone County. This is evidenced by the increase in the results of learning sprint (sprint) with a high score.